A method to predict the cyclic loading profiles (one-way or two-way) for monopile supported offshore wind turbines. (January 2019) - Jalbi, Saleh; Arany, Laszlo; Salem, AbdelRahman; Cui, Liang; Bhattacharya, Subhamoy
Abstract: Monopiles are currently the preferred option for supporting offshore wind turbines (OWTs) in water depths up to about 40 m. Whilst there have been significant advancements in the understanding of the behaviour of monopiles, the guidelines on the prediction of long term tilt (Serviceability Limit State, SLS) under millions of cycles of loads are still limited. Observations and analysis of scaled model tests identify two main parameters that governs the progressive tilt of monopiles: (a) Loading type (one-way or two-way) which can be quantified by the ratio of the minimum to maximum mudline bending moments (Mmin /Mmax ); (b) factor of safety against overturning i.e. the ratio of the maximum applied moment (Mmax ) to the moment carrying capacity of the pile or Moment of Resistance (MR ) and therefore the ratio Mmax /MR . Due to the nature of the environmental loads (wind and wave) and the operating conditions of the turbine, the ratio Mmin /Mmax changes. The aim of this paper is to develop a practical method that can predict the nature of loading for the following governing load cases: Normal Operating Conditions, Extreme Wave Load scenario, and Extreme Wind Load scenario. The proposed method is applied to 15 existing wind farms in Europe where (Mmin /Mmax ) and (Mmax /MR ) are evaluated. The results show that the loading ratio is sensitive to the water depth and turbine size. Furthermore, under normal operating conditions, most of the wind turbine foundations in shallow waters are subjected to one-way loading and in deeper waters and under extreme conditions the loading is marginally two-way. Predictions for the nature of loading for large wind turbines (8 MW and 10 MW) in deeper waters are also presented. The results from this paper can be used for planning scaled model tests and element tests of the soil. Highlights: Deterministic methodology to calculate minimum (Mmin ) and maximum (Mmax ) moments on a monopile due to wind and wave loads. Range of Mmin /Mmax for 15 operating wind turbines in normal operating conditions and extreme conditions. Prediction of (Mmin /Mmax ) for large wind turbines in deeper waters.